Analysis of Sharia Marketing Principles in the Sales of Cap Mikih Rice Products (Case Study of PT. Tunas Nabati Andalan Mukomuko) - Ardi Okta Putra (Sharia Economic and Management Business Journal (SEMBJ), 2025)
The purpose of this research is to determine the Sharia Marketing Principles in the Sales of Cap Mikih Rice Products. The research carried out was field research using qualitative descriptive methods. The data collection techniques used were observation, interviews and documentation. Then the data obtained is analyzed and discussed to answer the problems of this research. The results of this research show that the Principle of Unity (Tauhid), the company's business activities are moral in order to achieve blessings and is the most basic value in every business activity. This company is included in the marketing function, the Principle of Permissibility (Ibahah), the company prioritizes customer satisfaction with quality. good products, consumers feel satisfied and have confidence in the products being marketed, the company makes this principle the most important, the Principle of Justice (Al"Adl), the Company is based on market prices, from the prices of materials, processing, and several programs carried out. From the location of setting prices.